Autonomic modulation of chronic kidney patients on hemodialysis (Research, Society and Development, 2022)
Chronic kidney Disease may progress to cardiovascular complications just as much as these complications can result in further deterioration of the renal function, with dialysis as an extreme therapeutical option. Heart Rate Variability is a noninvasive method for the evaluation of sympathovagal imbalance of the heart beat control, aiding on the early detection of cardiovascular malfunctions. Our purpose was to identify heart rate variability patterns in chronic kidney disease patients undergoing hemodialysis treatment, both by linear and nonlinear analysis.Were sampled a group of 27 renal failure patients under hemodialysis care, and a control group of 21 healthy individuals. The RR intervals were captured with a Polar® device from subjects lying in supine position for 20 minutes. A total of 1000 consecutive intervals were selected, and both linear and nonlinear parameters were considered for the heart rate variability analysis. Were used Shapiro-Wilk test, Mann-Whitney test, and Spearman test. Among the findings with statistical significance, reductions were found in RMSSD and pNN50, and SD1 and SD2 indexes whereas increases in the recurrence percentage and in entropy could be observed. A significant negative correlation between age and the values of SD1 index was also found. Patients with renal failure present a lower autonomic modulation of the parasympathetic branch, as highlighted by both the linear and nonlinear analysis. The nonlinear indexes in the Chaos domain were more precise in identifying autonomic dysfunctions, can reflect more clearly the complexity of the organic systems.